2021
DOI: 10.1002/jcb.30074
|View full text |Cite
|
Sign up to set email alerts
|

R‐loops mediate transcription‐associated formation of human rDNA secondary constrictions

Abstract: The ribosomal gene DNA (rDNA) often forms secondary constrictions in the chromosome; however, the molecular mechanism involved remains poorly understood. Here, we report that occurrence of rDNA constriction was increased in the chromosomes in human cancer cell lines compared with normal cells and that decondensed rDNA was significantly enhanced after partial inhibition of rDNA transcription. rDNA transcription was found during the S phase when replication occurred, and thus, DNA replication inhibitors caused c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…Clearly, there is a causal relationship between RNase H1-deletion mediated R-loop enrichment and rRNA transcription elongation arrest. In addition, our previous studies suggested that the decreased expression of RNase H1 triggered the formation of multiple nucleoli (Zhou et al, 2020) and RNase H1 is implicated in bigger rDNA constriction formation (Zhou et al, 2021). Those above results further confirmed that loss of RNase H1 causes RNAP I transcription-associated R-loop accumulation along with suppressing rRNA transcription to trigger disordered and fragmented nucleoli.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Clearly, there is a causal relationship between RNase H1-deletion mediated R-loop enrichment and rRNA transcription elongation arrest. In addition, our previous studies suggested that the decreased expression of RNase H1 triggered the formation of multiple nucleoli (Zhou et al, 2020) and RNase H1 is implicated in bigger rDNA constriction formation (Zhou et al, 2021). Those above results further confirmed that loss of RNase H1 causes RNAP I transcription-associated R-loop accumulation along with suppressing rRNA transcription to trigger disordered and fragmented nucleoli.…”
Section: Resultssupporting
confidence: 72%
“…The secondary antibodies were the horseradish peroxidase (HRP) labeled goat anti-mouse IgG (A0126, Beyotime, Shanghai, China,) and the HRP labeled goat anti-rabbit IgG (A3327, Beyotime, Shanghai, China). Immunoreactivity was determined using the ECL method (K-12045-D50, advansta, California, USA) according to the manufacturer's instructions (Zhou et al, 2021).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…R-loops are transient, reversible structures that form in many regions of the genome. Predictors of R-loop presence include high transcriptional activity, open DNA and high GC content, all present in rDNA 66, 67 . R-loops participate in the regulation of transcription, but they also represent a potential source of damage, and their presence must be carefully regulated 68 .…”
Section: Discussionmentioning
confidence: 99%
“…The tandem arrays of rDNA have been observed as fragile sites and other complex macro-structures ( Ferraro et al, 1977 ; Warmerdam and Wolthuis, 2019 ; Zhou et al, 2021 ). Fragility induction at rDNA arrays by aphidicolin and actinomycin-D was recently demonstrated ( Zhou et al, 2021 ).…”
Section: Fragile Sites and Repeatsmentioning
confidence: 99%
“…The tandem arrays of rDNA have been observed as fragile sites and other complex macro-structures ( Ferraro et al, 1977 ; Warmerdam and Wolthuis, 2019 ; Zhou et al, 2021 ). Fragility induction at rDNA arrays by aphidicolin and actinomycin-D was recently demonstrated ( Zhou et al, 2021 ). The multiple clusters of tandem ribosomal DNA (rDNA) repeat arrays reside in the short arms of five of the 10 human acrocentric chromosomes, 13, 14, 15, 21, and 22 ( Boisvert et al, 2007 ; McStay, 2016 ).…”
Section: Fragile Sites and Repeatsmentioning
confidence: 99%